SEMNIFICAȚII PARADIGMATICE ALE RELAȚIEI GLOBALIZARE – TRANSFORMARE DEMOCRATICĂ - Saca, Victor (CEP USM, 2017)
In the present article are examined the key aspects of the present democratic transformations in the context of the global and national factors. There are analyzed the paradigms of globalization and transition and the democratic transformation, the value correlation including the typological one too between these two paradigms. In this context, the authors emphasize the systemic capacities of influence of the globalization upon the democratic transformations, as well as the reverse influences, meaning the respective transformations upon the globalization. Much of the article is dedicated to the relation among the global and national factors in the conditions of the sociopolitical transformation both in the former communistic and soviet countries. Each of the mentioned factors has its own peculiarities regarding their place and role in the relations and present sociopolitical transitions system. The role of these factors is determined not only by the character and the possibilities to initiate the relations of transformation, but also by the mutual connections in order to maintain and develop these relations continuously.
Keywords: democratic transformation; democratic transition; globalization; localization; the globalization-democratic transformations relation